Glucagon‐like peptide‐1, glucose‐dependent insulinotropic polypeptide, and glucagon receptor poly‐agonists: a new era in obesity pharmacotherapy. Issue 9 (24th July 2022) - Malik, Is‐haq O.; Petersen, Max C.; Klein, Samuel
Abstract: Achieving successful long‐term weight loss with lifestyle modification in people with obesity is difficult and underscores the need for effective pharmacotherapy. Since 1947, a total of 18 medications have been approved by the US Food and Drug Administration for treating obesity; however, only 5 remain available for long‐term use in the US. Semaglutide, a glucagon‐like peptide‐1 (GLP‐1) receptor agonist approved in 2021, demonstrated much greater weight loss than previous medications, which stimulated the development of poly‐agonists that combine GLP‐1 receptor agonism with glucose‐dependent insulinotropic polypeptide (GIP) and glucagon receptor agonism. The potential of this approach was recently demonstrated by the extraordinary weight loss achieved by tirzepatide, a GLP‐1/GIP receptor dual agonist. The therapeutic efficacy of poly‐agonists is likely to change the treatment paradigm for obesity. However, the use of medications for obesity, as for other chronic diseases, will likely require lifelong treatment, which makes it important to analyze the long‐term efficacy, safety, and economic implications of chronic pharmacotherapy.